Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7150/jca.67348
|View full text |Cite
|
Sign up to set email alerts
|

Number of Positive Lymph Nodes Combined with the Logarithmic Ratio of Positive Lymph Nodes predicts Survival in Patients with Non-Metastatic Larynx Squamous Cell Carcinoma

Abstract: Background: Logarithmic ratio of positive lymph nodes (LODDS), number of positive lymph nodes (NPLN), and number of lymph nodes to positive lymph nodes (pLNR) are three lymph node classifications; however, their function in prognosis is unclear. Purpose: To establish and validate an optimal nomogram according to the comparison among the 7 th TNM stage of American Joint Committee on Cancer (AJCC) and the three lymph node classifications. Methods: A total of 881 patients from the Surveillance, Epidemiology and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…AJCC nodal staging of the larynx is mainly based on the anatomical location of the lymph nodes (single or multiple, site, and size), without considering the absolute number and ratio of positive lymph nodes 22 . The limitations of the current laryngeal TNM staging system are highlighted by the data reported in our case study, which agrees with those published in similar studies 18,21,23,25,26 . In particular, the comparison of our patients based on pTNM revealed that there were no significant differences in terms of DSS and DFS in patients with stages I–III disease and that the only significant differences were observed for stages IVA and IVB.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…AJCC nodal staging of the larynx is mainly based on the anatomical location of the lymph nodes (single or multiple, site, and size), without considering the absolute number and ratio of positive lymph nodes 22 . The limitations of the current laryngeal TNM staging system are highlighted by the data reported in our case study, which agrees with those published in similar studies 18,21,23,25,26 . In particular, the comparison of our patients based on pTNM revealed that there were no significant differences in terms of DSS and DFS in patients with stages I–III disease and that the only significant differences were observed for stages IVA and IVB.…”
Section: Discussionsupporting
confidence: 89%
“…22 The limitations of the current laryngeal TNM staging system are highlighted by the data reported in our case study, which agrees with those published in similar studies. 18,21,23,25,26 In particular, the comparison of our patients based on pTNM revealed that there were no significant differences in terms of DSS and DFS in patients with stages I-III disease and that the only significant differences were observed for stages IVA and IVB.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations